The comparative importance of mental and physical disorders for health-related days out of role in the general population of Saudi Arabia - Yasmin A. Altwaijri; Victor Puac-Polanco; Abdullah S. Al-Subaie; Yasser Ad-Dab'bagh; Abdul Hameed Al-Habeeb; Lisa Bilal; Nancy A. Sampson; Andrew J. King; Somnath Chatterji; Ronald C. Kessler (BMC, 2022)
Abstract Background A major component of illness burden is role impairment. As part of the recently-completed Saudi National Mental Health Survey (SNMHS), we compare the number of days out of role in the Saudi population associated with ten core mental disorders assessed in the survey to those associated with ten commonly occurring chronic physical disorders. Methods The SNMHS was a household survey that assessed prevalence of ten common anxiety, mood, disruptive behavior, and eating disorders in a nationally representative sample of n = 1981 citizens of the Kingdom of Saudi Arabia (KSA) ages 15-65. Comparison information was obtained on prevalence of ten common chronic physical disorders and number of health-related days out of role (DOR) in the 30 days before interview. Generalized linear models were used to examine univariate and multivariable associations of disorders with DOR and to calculate population attributable risk (PAR) separately and overall for the disorders controlling for socio-demographics. Results 19.9% of respondents had one or more of the selected mental disorders and 47.1% had one or more of the selected physical disorders. Nine mental disorders and two physical disorders were associated with increased DOR. PAR was 32.9% for mental disorders, 27.0% for physical disorders, and 59.9% for both combined. Conclusions Mental disorders are associated with a substantial proportion of all health-related DOR in the Kingdom of Saudi Arabia. Programs to detect and treat mental disorders might lead to substantially decreased role impairment in the Kingdom.